On the Secrecy Performance and Power Allocation in Relaying Networks with Untrusted Relay in the Partial Secrecy Regime - Moya Osorio, Diana Pamela; Alves, Hirley; Benitez Olivo, Edgar Eduardo [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2020)
Recently, three useful secrecy metrics based on the partial secrecy regime were proposed to analyze secure transmissions on wireless systems over quasi-static fading channels, namely: generalized secrecy outage probability, average fractional equivocation, and average information leakage. These metrics were devised from the concept of fractional equivocation, which is related to the decoding error probability at the eavesdropper, so as to provide a comprehensive insight on the practical implementation of wireless systems with different levels of secrecy requirements. Considering the partial secrecy regime, in this paper we examine the secrecy performance of an amplify-and-forward relaying network with an untrusted relay node, where a destination-based jamming is employed to enable secure transmissions. In this regard, a closed-form approximation is derived for the generalized secrecy outage probability, and integral-form expressions are obtained for the average fractional equivocation and the average information leakage rate. Additionally, equal and optimal power allocation schemes are investigated and compared for the three metrics. From this analysis, we show that different power allocation approaches lead to different system design criteria. The obtained expressions are validated via Monte Carlo simulations.
Keywords: Amplify-and-forward; average fractional equivocation; average information leakage rate; generalized secrecy outage probability; partial secrecy regime; power allocation; untrusted relay